Adsorption and Photodegradation of Cationic and Anionic Dyes by TiO2-Chitosan Nanocomposite - Imelda Fajriati; Mudasir Mudasir; Endang Tri Wahyuni (Universitas Gadjah Mada, 2019)
The adsorption and photodegradation of cationic and anionic dyes by TiO2-chitosan nanocomposites have been studied. This study investigated the specific surface area, pores volume, pores size of TiO2-Chitosan nanocomposite, and determination kinetics of the reaction on the adsorption and photodegradation process. The methods were carried out by mixing TiO2-nanocomposite into cationic and anionic dyes in various contact times and initial dye concentrations. The results showed that nanocomposite adsorption capacity increased with an increase in the amount of chitosan (TiO2/Chit 0.13) even though the specific surface area (SBET) was reduced. The results indicated that the adsorption on nanocomposite was influenced by the amount of -NH2 and -OH on the chitosan surface. The maximum adsorption capacity (qm) and the observed reaction constant (kObs) for MO were also known to be higher than MB, which means that the TiO2-chitosan nanocomposites could remove anionic dye more than cationic one.